2020
DOI: 10.1155/2020/7574531
|View full text |Cite
|
Sign up to set email alerts
|

DE-CNN: An Improved Identity Recognition Algorithm Based on the Emotional Electroencephalography

Abstract: In the past few decades, identification recognition based on electroencephalography (EEG) has received extensive attention to resolve the security problems of conventional biometric systems. In the present study, a novel EEG-based identification system with different entropy and a continuous convolution neural network (CNN) classifier is proposed. The performance of the proposed method is experimentally evaluated through the emotional EEG data. The conducted experiment shows that the proposed method approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, ensemble classifiers are more effective than a single strong learner [238]. Thus, it is suggested that scholars should Second, machine learning and deep learning have been widely applied to EEG data analysis, particularly CNNs (e.g., [239][240][241][242][243][244][245]). CNNs are effective as function approximators and are commonly used to resolve classification issues involving EEG signal decoding for BCIs.…”
Section: Latest Research Concerning Ai-enhanced Eeg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ensemble classifiers are more effective than a single strong learner [238]. Thus, it is suggested that scholars should Second, machine learning and deep learning have been widely applied to EEG data analysis, particularly CNNs (e.g., [239][240][241][242][243][244][245]). CNNs are effective as function approximators and are commonly used to resolve classification issues involving EEG signal decoding for BCIs.…”
Section: Latest Research Concerning Ai-enhanced Eeg Analysismentioning
confidence: 99%
“…Hence, we can see that application of ANNs is relatively limited in the analysis of EEG data compared to CNNs. The application of CNNs in EEG studies includes intuitive robotic arm control [239], decode motor preparation of upper limbs [240], identity recognition [241], emotion recognition [242], decoding human brain activity [243], EEG motor imagery classification [244], and decoding EEG four-class motor imagery tasks [245].…”
Section: Latest Research Concerning Ai-enhanced Eeg Analysismentioning
confidence: 99%